Effectiveness of Smart Phone App for Selfassessment of Dry Eyes in Smartphone Users - Patel, Hemant; Shah, Rajul; R.N. , Kothari; Pathak, Mudra (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: Smart phone app (Dry Eye Relief) effectiveness for detection of dry eyes and self-monitoring of dry eyes in smartphone users. Methods: 250 cases with an age group of 18-35 years of age having access and comfort for using smartphones underwent Schirmer’s test, TBUT, and OSDI score test, along with a battery of tests performed using the app to assess the blink rate, blink interval, and subjective comfort with details on lifestyle, screen time, and contact lens use. We compare manual OSDI with App’s OSDI and classify the persons as having mild, moderate, or severe dry eyes. The clinical tests to diagnose dry eyes are compared with digital tests offered by the smartphone app. Results: Our study has maximum persons in the age group of 18-22 years with no sex predisposition. On comparison of our OSDI and App scores, both are equal (Pearson’s correlation) in diagnosing dry eyes, but patient satisfaction rate, ease of understanding, and less time-consuming were noted in App Score (0.873). We found a negative correlation between TBUT and blink rate (-0.830) but no correlation between blink interval (0.087) and TBUT. Also with Schirmer’s test we found a negative correlation with blink rate (-0.853) but no correlation between blink interval (0.082). Though TBUT (0.006) and Schirmer’s (0.1) lack a positive correlation with subjective discomfort, interestingly we found that patients with dry eyes can stare more at the screen than people with no dry eyes. Conclusion: The smartphone app is an effective means for screening of dry eyes by self-assessment and keeping track of its progressionn a tech-savvy population, as they are more vulnerable to dry eye and they are comfortable using such apps. But still, there is a need to standardize protocol and criteria for diagnosis of dry eye. It is free, handy, easy to use, and automated reporting for user understanding. Financial disclosures: No financial interests to be disclosed.